СОЦІАЛЬНИЙ РЕАЛІЗМ В УКРАЇНСЬКІЙ ЛІТЕРАТУРІ ХХ СТ. - Zhygun, Snizhana (Синопсис: текст, контекст, медіа, 2017)
The article deals with the phenomenon of social realism in the Ukrainian literature of the 20th century in order to give more precise definition to the ambiguous ideas of the stylistic picture of native literature in the 20th century. The phenomenon of social realism was the most considerable, though not the most original, as in "continental" literature (B. Antonenko-Davydovych), so in the Diaspora literature (U. Samchuk, D. Humenna. S. Domazar). The social realism is treated as a recurrence of the 20th century realism, esthetically anachronistic phenomenon in comparison with neo-realism. The significance of this phenomenon is connected first of all with ideology: in the conditions of colonial dependence of Ukraine, social realism, paying attention to the problems of class oppression, artistically interpreted also the national oppression. The narrative of national self-affirmation became the core of this current in the Ukrainian literature of the 20th century that often is implemented in the history of national consciousness formation (awakening). The Narodism (populism) which external sign is the attention to the idealized and aestheticized ethnoimages becomes an important ideological component of this current. The concept of the person also refers to the ideas urgent for realism of the 19th century: the character is formed by environment, and his mental life is defined by knowledge and experience. The social realism technique is oriented to the 19th century aesthetics. A teller often has unlimited knowledge, even if it displaces him from the real position. He is inclined to comment and interpret represented events influencing on a reader. Didacticism assisted the association of Ukrainians in community and formed nation after the sustained losses.